Knowledge level of pelvic floor and pelvic floor disorders according to and related disorders according to gender and education levels - YILDIZ ÖZER, AYSEL (My University, 2023)
Pelvic floor disorders, their management and protective educational programs have become popular in recent years. The aim of this study is to determine the level of knowledge about pelvic floor health according to gender and education levels. This cross sectional study is conducted on women and men between January and September of 2021 in Turkey. The knowledge level of pelvic floor was assessed with Pelvic Floor Health Knowledge Quiz (PFHKQ). Oneway ANOVA test was used for comparing pelvic floor knowledge according to the education levels and the age groups. Chi square test and Pearson chi square test were used for calculating binary variables, effect size, and confidence interval values between participants’ pelvic floor knowledge level and gender. A total of 1215 (1115 women, 100 men) participants completed the study. Men had less knowledge about the topics related to the pelvic floor (p <0.05) and the awareness of those that have graduated from higher education on these issues was found to be higher compared to the other education levels (p<0.05). In conclusion, we determined that the Turkish population has insufficient knowledge about the relationship between the pelvic floor and other body systems, the causes and types of pelvic problems. In the future, educational programs emphasizing deficient points regarding the pelvic floor within the scope of preventive treatment may be planned to cover the general population
Keywords: Sağlık Bilimleri; Fizyoterapi ve Rehabilitasyon; Health Sciences; Physical therapy and rehabilitation; Klinik Tıp (MED); Klinik Tıp; REHABİLİTASYON; Clinical Medicine (MED); CLINICAL MEDICINE; REHABILITATION; Fizik Tedavi, Spor Terapisi ve Rehabilitasyon; Kayropraktik; Rehabilitasyon; Physical Therapy, Sports Therapy and Rehabilitation; Chiropractics; Rehabilitation; Cardiovascular; Down Syndrome; Exercise; Physical Activity